2013
DOI: 10.1371/journal.pone.0083538
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Wheat Powder Induces the Antioxidant and Detoxifying System in Primary Rat Hepatocytes

Abstract: Many plants exhibit antioxidant properties which may be useful in the prevention of oxidative stress reactions, such as those mediated by the formation of free radical species in different pathological situations. In recent years a number of studies have shown that whole grain products in particular have strong antioxidant activity. Primary cultures of rat hepatocytes were used to investigate whether and how a fermented powder of wheat (Lisosan G) is able to modulate antioxidant and detoxifying enzymes, and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 68 publications
0
40
1
Order By: Relevance
“…Not only does this product contain the typical components of cereals but also after fermentation it is enriched in bioactive substances such as phenolic components and alpha-lipoic acid [13], a natural antioxidant that can provide protection against reactive oxygen species- (ROS-) induced vascular damage [14]. In healthy rabbits, LG improves lipid profile and antioxidant status [15], while in in vitro studies LG has been shown to exert protective effects in human microvascular endothelial cells exposed to oxidized-LDL controlling both oxidative and inflammatory processes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Not only does this product contain the typical components of cereals but also after fermentation it is enriched in bioactive substances such as phenolic components and alpha-lipoic acid [13], a natural antioxidant that can provide protection against reactive oxygen species- (ROS-) induced vascular damage [14]. In healthy rabbits, LG improves lipid profile and antioxidant status [15], while in in vitro studies LG has been shown to exert protective effects in human microvascular endothelial cells exposed to oxidized-LDL controlling both oxidative and inflammatory processes [16].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity of Lisosan G was previously evaluated through in vitro and in vivo experiments (Longo et al, 2007;Frassinetti et al, 2012;La Marca et al, 2013;Longo et al, 2014). Frassinetti et al (2012) demonstrated that Lisosan G removed the free radicals that originated from a normal aerobic metabolism and increased CAT, glutathione peroxidase (GPX) and superoxide dismutase (SOD).…”
Section: Discussionmentioning
confidence: 99%
“…Ethoxycoumarin-O-deethylase (ECOD), ethoxyresorufin O-deethylase (EROD), catalase (CAT), DT-diaphorase, glutathione-Stransferase (GST) and heme oxygenase-1 (HO-1) activities were measured as reported in La Marca et al (2013) and Vornoli et al (2014).…”
Section: Liver and Kidney Enzymes Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In our work, we explored the effects of Lisosan G. This product not only presents the above mentioned features of cereals, but is also enriched in bioactive compounds such as flavonoids, phenolic components and alpha-lipoic acid, since it derives from a fermentation process [81] . There, we evaluated the viability and cell function of endothelial progenitors and showed beneficial effects on both properties.…”
Section: Fermented Food: a New Class Of Nutraceuticals?mentioning
confidence: 99%